Philanthropic Fashion: Ireland, 1887–1897. (1st June 2014) - Helland, Janice
Abstract: During the nineteenth century a number of aristocratic women promoted British-made textiles by wearing garments made from domestic cloth. Royalty, too, regularly endorsed this British-made cloth by wearing gowns of British manufacture frequently trimmed with English or Irish lace. Beginning in the late 1880s, however, a more organized and sophisticated relationship developed between Irish textiles and fashion and, by the 1890s, this link was both assiduously promoted and systematically marketed. The Irish Industries Association, founded by Ishbel, Countess of Aberdeen in 1886 to promote craft and alleviate poverty in Ireland, was supported by a number of British and Irish aristocrats. The Association organized exhibitions in London, established a rapport with women's magazines, such as Lady's Pictorial, Gentlewoman and Queen, The Lady's Newspaper, and encouraged fashionable shops to view, buy and promote garments made from Irish wool, lace and linen. Thus Irish textiles moved from the Celtic fringe to the metropole, and from there on to the bodies of the rich and famous. It is this highly organized appeal to consumers that I shall explore here as philanthropy colluded with the market to produce fashion.